Percutaneous Biliary Drain Complications in Transplanted versus Native Liver: A Comparative Retrospective Study - Stumbras, Lauren Marissa; Quencer, Keith; Kaufman, Claire (The Arab Journal of Interventional Radiology, 2021)
Purpose The aim of this study was to assess the rate of complications of percutaneous transhepatic biliary drain in transplanted versus native livers.Materials and Methods A retrospective chart review was performed of all percutaneous transhepatic biliary drains completed at our institution from 2009 to 2018. Chart review of complications and interventions was recorded. Chi-squared and Fisher’s exact tests were used to compare percutaneous transhepatic biliary drains performed in patients with liver transplants (n = 62) to those with native livers (n = 285).Results There was a statistically significant difference in the frequency of complications of percutaneous transhepatic biliary drains in patients with liver transplants (61%) compared with those with native livers (13%), χ2(1) = 9.59, p<0.01. There was a statistically significant increased frequency of worsening liver function, sepsis, bile leak, arterial and portal venous bleeds, and secondary complications in those with liver transplants. The median number of days until the complication occurred for those with liver transplants was nearly three times longer than those with native livers. The most common subsequent intervention for patients with liver transplants was placement of a new drain (53%), whereas those with native livers was drain upsize (70%).Conclusion Complications including vascular injury, sepsis, bile leak, and worsening liver function after percutaneous transhepatic biliary drains occurred more commonly in patients with liver transplants versus native livers.
Keywords: percutaneous transhepatic biliary drain; hepatobiliary; liver transplant